Peran Harmonisasi Hukum dalam Pengaturan Standar Pelayanan Kesehatan - Gilang Setia Anggara; Mohammad Rifqillah; Arya Surya Permana Putra; Vira Amanda Putri; Wahyu Angelina Agustine (Fakultas Hukum, UPN Veteran Jawa Timur, 2024)
Health services are a fundamental component in realizing a nation’s welfare and social justice. The state holds an essential role in ensuring access to and protection of healthcare for all its citizens. However, the implementation of health law becomes hindered when complex challenges arise, particularly due to overlapping regulations and rapid technological developments. Various regulations have been introduced as part of national law to harmonize healthcare service standards and legal protection for all parties involved. This study employs a normative approach with a literature-based method to examine the harmonization of healthcare service standards. The fragmented regulatory framework can obstruct the implementation of health law; therefore, legal harmonization is crucial to ensure legal certainty, legal protection, service standards, and the integrity of the national healthcare system. The success of legal harmonization is vital to guarantee legal certainty, effective service delivery, and the protection of the rights and responsibilities of all parties within the healthcare system, in accordance with constitutional mandates. Keywords: Legal Harmonization; Health Law; Health Services.